Himalayan fermented foods : microbiology, nutrition, and ethnic values - Tamang, Jyoti Prakash (CRC Press, 2010)
Catalogs the wide array of extensively studied fermented items found in the Himalayas, including fermented fish and vegetables. This book isolates, characterizes, and identifies each probiotic microorganism based on modern phenotypic and genotypic characteristics.